Population parameters based on known pedigree records from Brazilian Jaffarabadi buffaloes - Malhado, Carlos Henrique Mendes; Ferraz, P. C.; Ramos, A. A. [UNESP]; Carneiro, P. L.S.; Aragão, E. S.; Barbosa, A. C.B.; Carrillo, J. A. (Int Buffalo Information Ctr, 2013)
The objective of this study was to evaluate the effective number of founders and ancestors, generation intervals and completeness of pedigree in Jaffarabadi breed buffaloes raised in Brazil. Pedigree records of 1,272 animals born from 1966 were used. The parameters were estimated using ENDOG, computational population genetic software. The obtained value for completeness of pedigree was 99.5, 50.9, and 20.5 for, the first, second and third generations, respectively. Generation interval estimates expressed in years and considering different pathways were 12.28±6.90 (sire-son), 11.55±6.07 (sire-daughter), 8.20±2.63 (dam-son) and 8.79±4.33 (damdaughter). The overall average generation interval was 10.17±5.43 years. The number of founders, equivalent founders and ancestor animals that contributed for the genetic diversity in the reference population (1059) were 136, 130 and 134, respectively. Effective number of founder (fe=8) and ancestors (fa=7) were small, and the calculated expected inbreeding increase per generation was 4.99%. Four ancestors explained 50% of the genetic variability in the population and the major ancestor contributed with approximately 33% of the total population genetic variation. The genetic diversity within the current population is low as a consequence of a reduced number of ancestors.
Keywords: Ancestors; Founders; Generation interval